Rat Urinary Bladder Carcinogenesis by Dual-Acting PPARα+γ Agonists. (27th January 2009) - Oleksiewicz, Martin B.; Southgate, Jennifer; Iversen, Lars; Egerod, Frederikke L.
Abstract : Despite clinical promise, dual-acting activators of PPARα andγ (here termed PPARα +γ agonists) have experienced high attrition rates in preclinical and early clinical development, due to toxicity. In some cases, discontinuation was due to carcinogenic effect in the rat urothelium, the epithelial layer lining the urinary bladder, ureters, and kidney pelvis. Chronic pharmacological activation of PPARα is invariably associated with cancer in rats and mice. Chronic pharmacological activation of PPARγ can in some cases also cause cancer in rats and mice. Urothelial cells coexpress PPARα as well as PPARγ, making it plausible that the urothelial carcinogenicity of PPARα +γ agonists may be caused by receptor-mediated effects (exaggerated pharmacology). Based on previously published mode of action data for the PPARα +γ agonist ragaglitazar, and the available literature about the role of PPARα andγ in rodent carcinogenesis, we propose a mode of action hypothesis for the carcinogenic effect of PPARα +γ agonists in the rat urothelium, which combines receptor-mediated and off-target cytotoxic effects. The proposed mode of action hypothesis is being explored in our laboratories, towards understanding the human relevance of the rat cancer findings, and developing rapid in vitro or short-term in vivo screening approaches to faciliate development of new dual-acting PPAR agonist compounds.